Mental Representation of Stimuli Austrian and Swiss Humour. - Zubach, Oksana (Hryhorii Skovoroda University in Pereiaslav, 2025)
The purpose of the study is to analyse linguistic consciousness, the specificity of cross-cultural communication, the role of humour as a social product of language, and culture and a person’s mentality identification, which is formed under the influence of psycholinguistic elements of perceiving the world and acquiring knowledge about it. Special attention has been given to studying the specificity of perceiving the Austrian and Swiss humour and their identification in the German-speaking space through the stimuli Österreichischer Humor and Schweizer Humor. Research methods and techniques. The research utilises the following theoretical methods: the structural-functional analysis of lexical units and the methods of systematization and modelling. We used the word association test to study the specificity of perceiving and singling out the stimuli Österreichischer Humor and Schweizer Humor in the German-speaking space in the consciousness of Ukrainian respondents. Results. It is proved that the stimuli under analysis are representatives of the conceptual awareness of the existence of the Austrian and Swiss humour in the German-speaking space and can be traced to the worldview of a Ukrainian linguistic personality. Due to typical and individual reactions of the respondents it was identified that the image of the Austrian and Swiss humour and its value orientations in the German-speaking space are shaped in their consciousness. Conclusions. We proved that the concept of Austrian and Swiss humour was shaped in the consciousness of the non-native speakers due to their practical and educational activities, educational processes and different levels of experience. The stimuli under analysis evoked typical, non-typical and individual reactions, indicating different principles of mental representation formation, rational awareness and emotional perception of the German-speaking space and the specificity of marking the elements of the identity of humour culture by a person.
Keywords: humour; stimulus; cross-cultural communication; linguistic-cultural analysis; psycholinguistic analysis; 81’23:[130.2:316.77](436+494)